Plant Diversity and Carbon Stocks in Urban Green Open Space (Case Study in PT. Gajah Tunggal Tbk., Tangerang, Banten) - Nur Muhammad Heriyanto; Ismayadi Samsoedin; Yanto Rochmayanto (Jurnal Sylva Lestari, 2023)
Efforts to mitigate climate change, namely reducing greenhouse gas emissions, can be carried out, among others, by utilizing trees in urban areas, which have an important role as carbon sinks. In order to determine the potential of tree species in absorbing carbon, research was conducted in the green open space area of PT. Gajah Tunggal Tbk. in Tangerang, Banten Province. This study aimed to determine the potential of tree species in absorbing carbon by measuring the diameter and height of 150 plant species of 46 families, consisting of 8,636 tree stands and 5,254 bamboo stems. The average age of the tree is over 7 years. The results showed that the potential biomass, carbon content, and CO2 absorption of plants with a diameter of 2 cm were dominated by Eucalyptus deglupta, Roystonea regia, and Pterocarpus indicus. The total biomass, carbon content, and CO2 absorption of tree and bamboo species were 880.82 tons or 413.98 tons C, equivalent to 1,519.33 t.CO2-eq. This company’s CO2 emissions in 2020 amounted to 406,073.72 t.CO2-eq. Keywords: Carbon stock, greenhouse gas, green open space, plant diversity